Cinema in democratizing Germany : reconstructing national identity after Hitler - Fehrenbach, Heide (Chapel Hill : University of North Carolina Press, 1995)
Heide Fehrenbach analyzes the important role cinema played in the reconstruction of German cultural and political identity between 1945 and 1962. Concentrating on the former West Germany, she explores the complex political uses of film--and the meanings attributed to film representation and spectatorship--during a period of abrupt transition to democracy. According to Fehrenbach, the process of national redefinition made cinema and cinematic control a focus of heated ideological debate. Moving beyond a narrow political examination of Allied-German negotiations, she investigates the broader social nexus of popular moviegoing, public demonstrations, film clubs, and municipal festivals. She also draws on work in gender and film studies to probe the ways filmmakers, students, church leaders, local politicians, and the general public articulated national identity in relation to the challenges posed by military occupation, American commercial culture, and redefined gender roles. Thus highlighting the links between national identity and cultural practice, this book provides a richer picture of what German reconstruction entailed for both women and men [Publisher description].
Introduction : Cinema and national identity, 1945-1962 -- Cinema and German society before 1945 -- From military surveillance to self-supervision : American occupation and the politics of film, 1945-1949 -- Die Sünderin or who killed the German man? : early postwar cinema and the betrayal of fatherland -- The fight for the "Christian west" : film control and the reconstruction of civil society -- Popular cinema, spectatorship, and identity in the early 1950s -- From feckless masses to engaged critics : German film clubs and the quest for cultural renewal -- Local challenges to the dominant culture : Mannheim, Oberhausen, and the stirrings of young German cinema -- Mass culture and cold war politics : the Berlin film festival of the 1950s.
Includes bibliographical references (pages 329-349) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Motion pictures -- Political aspects -- Germany (West); Motion pictures -- Social aspects -- Germany (West); Motion pictures -- Germany (West) -- History; Cinéma -- Aspect politique -- Allemagne (Ouest); Cinéma -- Aspect social -- Allemagne (Ouest); Cinéma -- Allemagne (Ouest) -- Histoire; PERFORMING ARTS -- Film & Video -- Reference; Motion pictures; Motion pictures -- Political aspects; Motion pictures -- Social aspects; Germany (West); Deutschland; Film; Filmkunst; Nationale identiteit; Motion pictures -- Political aspects -- Germany; Motion pictures -- Social aspects -- Germany; Motion pictures -- Germany -- History; Deutschland <Bundesrepublik>; Cinema -- Films (Motion pictures) -- History; Germany (Federal Republic); History